Collaboration and competition in business ecosystems - Adner, Ron; Oxley, Joanne E., 1961-; Silverman, Brian S. (Emerald, 2013)
The research featured in this volume is devoted to understanding the competitive and collaborative challenges that firms face as they manage interactions with different actors in dynamic environments, in what are coming to be referred to as business or innovation ecosystems. Rapid technological change, globalization, and recent financial turbulence have brought us to a point where managers are painfully aware that no man [or firm] is an island. Success in business, in both the profit and non-profit sectors, increasingly relies upon collaboration with upstream suppliers, alliance partners, and downstream complementors. This volume presents new findings of how innovation and value are created in collaborative networks, specifically ecosystem analysis and the unique roles of individual actors within this system.
Keywords: Business networks.; Strategic alliances (Business); Strategic planning.; elektronické knihy; electronic books